Investigation on the dissemination of unit watt in airborne sound and applications - Brezas, Spyros (Logos Verlag Berlin, 2019)
Sound power describes the emission of sound from sound sources. Despite today's state-of-the art measurement techniques, the current sound power determination methods are restricted due to various limitations. To overcome these limitations, a new sound power determination method is proposed, aiming at the establishment of traceability in airborne sound. This will enable the characterization of a sound source by its free field sound power. The dissertation describes a study on the dissemination process, which will allow the sound power of a device under test located at a real surrounding environment, to be referred to its free field sound power. Apart from the sound power, the corresponding uncertainty may be estimated in a transparent way, where each uncertainty component is provided. The basic tool for the dissemination process is the substitution method using aerodynamic reference sound sources, applied to both sound pressure and sound intensity measurements. Initially, a theoretical investigation deals with the factors that influence the substitution method. Experimental results are then presented based on measurements using a specially designed scanning apparatus. The transition from calibration to in situ conditions and the required correction, due to changes in environmental and operational conditions, is then discussed. In the last section, the sound power level of devices under test is determined along with its related uncertainty, which is further compared to the up-to-date uncertainty values.